2017
DOI: 10.1016/j.funeco.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Specialist taxa restricted to threatened habitats contribute significantly to the regional diversity of Peltigera (Lecanoromycetes, Ascomycota) in Estonia

Abstract: The widespread cyanolichen genus Peltigera comprises many insufficiently known poorly delimited and/or undescribed species. Phylogenetic analysis of 252 Peltigera specimens from a wide range of habitat types in Estonia revealed 31 putative taxa (OTUs). Multivariate analysis revealed habitat-specific segregation between the Peltigera species along a gradient from humid eutrophic forests to dry oligotrophic forests and grasslands and along a soil pH gradient from alkaline soils of alvar grasslands to acidic soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 74 publications
3
29
0
Order By: Relevance
“…Whether Peltigera singletons represent distinct species or artifacts of the implemented methods awaits further testing based on additional samples bridging the current localities (often distant) and using complementary methods that rely on other models with different assumptions. Our analyses confirmed that some taxa introduced informally in previous studies (Miadlikowska & Lutzoni, 2000;Jüriado & al., 2017) represent undescribed species, or assemblages of undescribed species, delimited consistently by multiple methods (e.g., Peltigera "fuscopraetextata", P. "neocanina" and P. "neorufescens"). Other provisionally named taxa should be merged (as indicated by , such as P. "pallidorufescens", which is synonymous with P. "fuscopraetextata", and P. "fuscoponojensis" which is nested within the P. "neorufescens" clade.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Whether Peltigera singletons represent distinct species or artifacts of the implemented methods awaits further testing based on additional samples bridging the current localities (often distant) and using complementary methods that rely on other models with different assumptions. Our analyses confirmed that some taxa introduced informally in previous studies (Miadlikowska & Lutzoni, 2000;Jüriado & al., 2017) represent undescribed species, or assemblages of undescribed species, delimited consistently by multiple methods (e.g., Peltigera "fuscopraetextata", P. "neocanina" and P. "neorufescens"). Other provisionally named taxa should be merged (as indicated by , such as P. "pallidorufescens", which is synonymous with P. "fuscopraetextata", and P. "fuscoponojensis" which is nested within the P. "neorufescens" clade.…”
Section: Discussionsupporting
confidence: 90%
“…neocanina corresponds to our P. "neocanina" 4, collected in Norway and Iceland. Apart from the hyperdiverse P. "neorufescens" complex, all lineages detected in section Peltigera by Jüriado & al. (2017) were also sampled in our study.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations